Speed-Accuracy Tradeoff Operator Characteristics of Endogenous and Exogenous Covert Orienting of Attention - Peter A. McCormick; Lori Francis (The Scientific World Journal)
There is debate over the mechanisms that govern the orienting of attention. Some argue that the enhanced performance observed at a cued location is the result of increased perceptual sensitivity or preferential access to decision-making processes. It has also been suggested that these effects may be the result of trades in speed for accuracy on the part of the observers. In the present study, observers performed either an exogenous or an endogenous orienting of attention task under both normal instructions (respond as quickly and as accurately as possible) and speeded instructions that used a deadline procedure to limit the amount of time observers had to complete a choice reaction time (CRT) task. An examination of the speed-accuracy operating characteristics (SAOCs) yielded evidence against the notion that CRT precuing effects are due primarily to a tradeoff of accuracy for speed.